Gold nanoparticles are suitable cores for building tunable iminosugar multivalency. Issue 116 (6th November 2015) - Matassini, C.; Marradi, M.; Cardona, F.; Parmeggiani, C.; Robina, I.; Moreno-Vargas, A. J.; Penadés, S.; Goti, A.
Abstract : Inhibition in the low micromolar range towards amyloglucosidase. Abstract : The first example of iminosugars multimerization based on gold nanoparticle cores was achieved by a straightforward synthetic strategy based on the use of simple glycosides of α-d -mannose or β-d -glucose to modulate the density of biologically active pyrrolizidine and piperidine iminosugars at the gold surface. Exceptionally small and water dispersible gold colloids were obtained by self assembly of thiol ending sugar and novel iminosugar conjugates on the surface of in situ forming gold nanoparticles. The resulting nanostructures were characterized by different techniques. Preliminary screenings demonstrated that the novel nanosized architectures retain their bioactivity and make possible its modulation.